KUALITAS PELAYANAN KESEHATAN KEPADA PESERTA BPJS KESEHATAN KELAS II YANG BERADA DI RUANGAN MAWAR RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Muhammad Ilham Kurniawan (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2021)
This study aims to determine the quality of service to patients using BPJS Kesehatan and to determine the inhibiting factors in providing quality service to patients using Class II BPJS Health who are in the Mawar Room of the Arifin Achmad Regional General Hospital, Riau Province. The method used in this research is mixed methods. Determination of respondents in the study using the census method where the number of respondents focused on inpatients using Class II BPJS Kesehatan in the Mawar Room. BPJS Kesehatan Class II participants became the focus of the study. Based on data obtained from the Regional General Hospital Arifin Achmad, Riau Province, it was found that there were 61 patients who were treated in the rose room, while for the research informants, 1 employee was the medical data processing coordinator, and 1 Hospital patient registration staff. The results showed that the quality of health services received by patients using BPJS Kesehatan Class II Mawar Room was considered good. This is illustrated by the 5 dimensions used in this study, namely: the reliability dimension, the responsiveness dimension, the assurance dimension, the empathy dimension, the tangibles dimension. Factors that hinder health services for the Arifin Achmad Regional General Hospital in Riau Province include System Factors, Procedures and Regulations, and Facility and Infrastructure Factors.